PENGEMBANGAN WEB SERVICE MENGGUNAKAN FRAMEWORK FASTAPI UNTUK MENINGKATKAN KEMUDAHAN INTEGRASI SISTEM INFORMASI AKADEMIK MULTIPLATFORM - Safitri, Aprilyani Nur; Harkespan, Imanuel (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2024)
Academic activities at Dian Nuswantoro University are managed using a web-based and mobile-based (Android and IOS) academic information system for students, lecturers, educators, and parents (guardians). The data retrieval process used by the academic information system is currently in each system itself so that it is prone to errors. Therefore, a back-end service is needed in the form of a web service that acts as a portal for the data retrieval process that can be used by the multiplatform academic information system. In addition to helping to avoid data retrieval errors, the web service that is built also provides complete and easy-to-understand documentation of web service usage. The average time required for the web service to provide a response when accessed by 1000 users is 6198ms (minimum 17ms and maximum 10017ms), meaning that the web service has good performance under high loads. The Extreme Programming method was chosen for the development of the web service in this study. This method consists of four stages, namely planning (analysis of what the system needs), design (visualization with Use Case diagrams), coding (using FastAPI Framework), and the last is testing (using BlackBox and JMeter for testing functions and security). The simplicity of this method can support the achievement of the desired results, namely a back-end service in the form of a web service, which can be used by a multi-platform academic information system to exchange data easily and accurately so that errors can be avoided, especially inconsistencies in presenting academic data.